The mediating role of work-family conflict in the relationship between supervisor support and job satisfaction - Ahmad, Aminah; Tengku Abdul Hamid, Tengku Aizan; Ismail, Azahari; Ngah, Noryati (2010)
With the increase in single mother employees, there has been an increased concern over the work-family conflict that they experience in trying to balance the demands of work and family roles. Recognizing the impact of the conflict on job satisfaction and the need for supervisor support, this study examines the interrelationships between these variables, and the mediating role of work-family conflict in the relationship between supervisor support and job satisfaction. Data were gathered from 159 Malaysian single mother employees, aged 45 and below, using self-administered questionnaires. Results of correlation analyses reveal that work-family conflict is negatively related to supervisor support (r=-.23; p<.05) and job satisfaction (r=-.35; p<.05), and supervisor support is positively related to job satisfaction (r=.19; p<.05). Results of regression analyses indicate that work-family conflict mediates the relationship between supervisor support and job satisfaction. Supervisor support leads to a reduction in work-family conflict (β=-.23; p<.05) which in turn leads to a reduction in the level of job satisfaction (β=-.32; p<.05). The results suggest the importance of providing social support at the workplace to help single mother employees reduce the conflict that they experience and subsequently increase their job satisfaction.